Education, work and social capital : towards a new conception of vocational education - Winch, Christopher [Verfasser] (Routledge, 2005)
This book provides an integrated treatment of the relationship between political economy and vocational education at the beginning of the twenty-first century. Approaching the subject from a philosophical perspective the author engages with debates about the work-related aims of education; the moral and spiritual significance of work; the conceptualisation of political economy; high-skill economies and vocational education; the "end of work" thesis; the relationship between education and training in vocational education; future work patterns; and the educational consequences of the economic theories of influential economists such as Smith, Mill, List, Marx, Marshall and Keynes. (BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; G 1.2 Arbeitsmarkt; T 4.1 Philosophie; G 2.1.1 Ökonomie / Märkte; T 4.5 Soziologie; Berufsbildung; Arbeitswelt; Lernen am Arbeitsplatz; Beziehung Bildungssystem Beschäftigungssystem; Philosophie; Ökonomie; Sozialkapital